Breaking Convention: A Multidisciplinary Conference on Psychedelic Consciousness edited by Cameron Adams, Dr. Ben Sessa and Anna Waldstein - Strassman, Rick (Journal of Scientific Exploration, 2014)
Psychedelic drugs disappeared as quickly from the public eye in the early 1970s as they had burst into the consciousness of the 1960s. At first touted as a key to mental illness, creativity, and spirituality, LSD and other psychedelic drugs became anathema due to their association with civil unrest, and psychiatric and other medical morbidity. As a result, clinical and other research into their effects ceased with their placement into an inaccessible legal status in the U.S. and in Europe in 1970. The current resurgence of medical research with psychedelics has received generally positive media treatment and benign government oversight. As a result, psychedelic drugs are once again being discussed in academic circles.